2018
DOI: 10.1186/s12974-017-1051-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia induces IL-1β overproduction via activation of NLRP3 inflammasome: implication in cognitive impairment in hypoxemic adult rats

Abstract: BackgroundCognitive impairment is one of common complications of acute respiratory distress syndrome (ARDS). Increasing evidence suggests that interleukin-1 beta (IL-1β) plays a role in inducing neuronal apoptosis in cognitive dysfunction. The lung protective ventilatory strategies, which serve to reduce pulmonary morbidity for ARDS patients, almost always lead to hypercapnia. Some studies have reported that hypercapnia contributes to the risk of cognitive impairment and IL-1β secretion outside the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 36 publications
4
71
1
1
Order By: Relevance
“…The present rat and cell models of hypercapnia/hypoxemia were established as described in our previous study. In the models, PO 2 levels of the arterial blood and culture supernatant were maintained at 55-60 mmHg and pH levels of the arterial blood and culture supernatant at 7.20-7.25 [9]. These are consistent with the change of hypoxemia and permissive hypercapnia in ARDS [25][26][27][28].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The present rat and cell models of hypercapnia/hypoxemia were established as described in our previous study. In the models, PO 2 levels of the arterial blood and culture supernatant were maintained at 55-60 mmHg and pH levels of the arterial blood and culture supernatant at 7.20-7.25 [9]. These are consistent with the change of hypoxemia and permissive hypercapnia in ARDS [25][26][27][28].…”
Section: Discussionsupporting
confidence: 70%
“…We reporeted in our previous study that hypercapnia-induced NLRP3 inflammasome activation in hypoxia-activated microglia could upregulate the expression of IL-1β. It is well documented that IL-1β promotes a cascade of inflammatory response in the central nervous system that can lead to the aggravation of neuronal injury [9]. Under hypoxic conditions, ROS is known to be critical for NLRP3 inflammasome activation [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ventilation strategy will certainly result in hypercapnia, which is called "permissive hypercapnia" [7,8]. Our previous study found that hypercapnia could induce IL-1β overproduction in hypoxia-activated microglia [9]. However, the underlying mechanism has remained unclear.…”
Section: Introductionmentioning
confidence: 99%